Saving the Mahachai Betta: Genetic Erosion and Conservation Priorities Under Urbanization Pressure - Ton Huu Duc Nguyen; Trifan Budi; Tavun Pongsanarm; Thitipong Panthum; Worapong Singchat; Narongrit Muangmai; Aingorn Chaiyes; ‪Warong Suksavate; Sahabhop Dokkaew; Darren K. Griffin; Prateep Duengkae; Kornsorn Srikulnath (Animals, 2025)
BACKGROUND/OBJECTIVES: ) is a bubble-nesting fighting fish endemic to brackish habitats in Bangkok, Samut Sakhon, and Samut Prakan, where rapid urbanization and industrial growth threaten persistence. We evaluated genetic structure and diversity across 10 populations (81 individuals) to inform conservation planning. METHODS: This study combined microsatellite genotyping (13 loci) with ecological niche modeling to assess genetic variability, population connectivity, and landscape-environmental drivers of differentiation. RESULTS: values up to 0.400. Forward simulations predicted severe erosion of diversity within the next 12.5-37.5 years. Populations showed clear genetic subdivision, most pronounced in Samut Prakan and Samut Sakhon, with two Samut Sakhon populations (SKN3 and SKN7) reflecting strong environmental heterogeneity. CONCLUSIONS: Improving habitat connectivity and intensifying local community engagement are priority actions to enhance the resilience and long-term persistence of Mahachai Betta. This study provides the first integrated genetic and landscape-based assessment of the species, highlighting its rapid genetic erosion under urbanization and offering a foundation for targeted, evidence-based conservation strategies.
Keywords: Genetic diversity and population structure; Fish Ecology and Management Studies; Environmental DNA in Biodiversity Studies